Dual Stressors and Female Pre-school Teachers' Job Satisfaction During the COVID-19: The Mediation of Work-Family Conflict - Hong, Xiumin; Liu, Qianqian; Zhang, Mingzhu (Frontiers in Psychology, 2021)
Online education has become a vital weapon to fight against the COVID-19 epidemic in the world. In the home-based online education environment, female preschool teachers are expected to balance the dual roles of teacher and mother at the same time, which may trigger the work-family conflict. Although previous studies analyzed individual stressors, work-family conflict and its outcomes, there is little research on preschool teachers’ work and parenting experience during major public health emergencies. The current study examined the associations among work overload, parenting stress, work-family conflict, and job satisfaction during the COVID-19. 718 female preschool teachers with children who worked online at home participated in the study. Female preschool teachers reported that the COVID-19 has increased work overload and parenting stress. Moreover, work overload was negatively associated with job satisfaction via its positive association with work-to-family conflict. Parenting stress was negatively associated with job satisfaction via both family-to-work conflict and work-to-family conflict. The study contributes to a better understanding of the association among female preschool teachers’ work overload, parenting stress, work-family conflict, and job satisfaction. Our findings highlighted potential avenues for interventions aimed at balancing female preschool teachers’ work and family and improving their job satisfaction during the COVID-19.